Key Approaches to the Study of History of Altai in 18th Century in Modern Russian Historiography - D. S. Bobrov; L. G. Zaitseva (Научный диалог, 2020)
The article is devoted to a comprehensive examination of theoretical approaches to the study of the history of Altai in the 18th century, developed by Russian specialists over the past three decades. The relevance of the study is associated with the emerging trend in domestic science towards a holistic understanding of the retrospective of individual regions, including through understanding the interdependent role of various social and administrative factors in the colonization process. Special attention is paid to the conceptual assessment of the nature of the initial development of Altai. The methodological grounds for applying the theories of military colonization, frontier, frontier modernization to the history of the region are outlined. The authors state the presence in the scientific literature of two non-identical approaches to the characterization of the Russian border in the south of Western Siberia. The authors demonstrate the obvious desire of historians to carry out comprehensive studies of regional and local levels of civil and mining management, which has emerged against the background of the preservation of the heuristic significance of microhistorical analysis of the role of individual fortified (fortresses, forts) or production facilities (factories). The diversity and conceptual heterogeneity of modern Russian historiography of the history of Altai in the 18th century is summarized. Some forecasts of the development of the historiographic situation are formulated.